Constraints on density changes in the funnel-shaped caldera inferred from gravity monitoring of the Lusi mud eruption. (February 2018) - Mauri, Guillaume; Husein, Alwi; Mazzini, Adriano; Karyono, Karyono; Obermann, Anne; Bertrand, Guillaume; Lupi, Matteo; Prasetyo, Hardi; Hadi, Soffian; Miller, Stephen A.
Abstract: From its inception May 29, 2006, the Lusi mud eruption has continuously erupted fluids, boiling mud and clasts through large active vents approximately 100 m in diameter. In 2016, we conducted a Dynamic Gravity survey (DG) using a network built over four locations and two Continuous Gravity-monitoring (CG) experiments to monitor the eruption activity. The CG was done for 8 days from June 2nd to June 10th, and for 9 days from August 20th to August 29th, 2016. Atmospheric pressure and atmospheric temperature variations were recorded during each experiment to constrain potential environmental effects, and Earth and oceanic tide effects were removed from gravity signals (CG and DG). Atmospheric pressure effects were removed from CG gravity signals. At the station, closest to the hydrothermal pond, the DG survey results show a gravity increase of ∼0.009 mGal month −1, which we interpret as the growth of the mud edifice in the central area. CG-monitoring shows that gravity variations occur at a period of 12–13 h, with amplitudes reaching up to 0.020 mGal. We interpret this as relating to density variation of the rising mud mixture (fluids + coarse mud + clasts). The observed 12–13 h period variations appear to indicate that tides may have some control on the density change of rising mud mixture by triggering the release of gas trapped at depth. Our 3D gravity results around the Lusi vents show that density variations range from 100 kg m −3 to 775 kg m −3 . Similarly, vent diameters better constrain density contrasts occurring within the caldera zone, which is more likely to range between 400 and 450 kg m −3, and is equivalent respectively to 27% and 31% of gas ratio change over time. Highlights: Gravity monitoring of ongoing mud eruption. 3D model of gravity variations to constrain density variation in the rising mud. Interpretation of gas, mud ratio based on density variation. Evolution of the gravity signal over time.